Climate Trauma and Habits Toward Hope: A Decolonizing Earth-Centered Approach - McCarroll, Pamela R. (Journal of pastoral theology, 2025)
Climate change is fueled by ongoing colonial systems of domination embedded incapitalism, threatening both human and more-than-human life. Trauma theory suggests that, when faced with overwhelming threat, humans often default to fight, flight, or freeze responses—reactions that can obscure the reality of the climate crisis and allow destructive systems to persist. This paper explores the intersections of colonialism, climate change, and trauma, examining how trauma responses manifest in the face of ecological collapse, including in theological expressions of hope. Drawing on trauma recovery models and earth-centered motifs, it proposes decolonizing, trauma-informed practices that support sustained engagement with the climate crisis. How can individuals and spiritual communities cultivate the capacity to “stay with the trouble” (Haraway) and act for life’s flourishing, even amid destruction? The paper invites a reimagining of hope—not as escapism, but as a grounded, relational practice for living well in the Anthropocene.